EFEKTIVITAS KONSELING KELOMPOK MENGGUNAKAN TEKNIK ROLE PLAY UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Nadiyya, Nadiyya; Wicaksono, Luhur; Fergina, Ana (Universitas Tanjungpura, 2023)
This study aims to test the effectiveness of group counseling using role play technique to increase the learning motivation of class VII students of SMPN 3 Pontianak. The research method was an experiment with a One-Group Pretest-Posttest Design. The data collection technique used a questionnaire with a Likert scale, then validity and reliability tests are carried out on the questionnaire. The population of this study was class VII G students at SMP Negeri 3 Pontianak who were categorized as having low learning motivation. The sampling technique used Nonprobability Sampling technique the type of Purposive Sampling in which a sample was taken of 9 people who were in the low category. The results showed that the level of motivation to learn before the group counseling in the role play technique was 61 and after the group counseling was 101.22. The results of hypothesis test using the Wilcoxon test statistic obtained a sig value (2-tailed) 0.007. Then Ha is accepted and Ho is rejected, which means there is a significant difference between students' learning motivation before and after being given group counseling using role play technique. It can be concluded that group counseling with role play techniques is effective in increasing the learning motivation of class VII students of SMPN 3 Pontianak